Research on the variation in the employees’ work motivation, depending on the bio-psychosocial development stage - Diaconescu, Laura Maria; Martins, Dora; Panoiu, Laura (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
The innovative performance of a company in the current century, in line with the Europe 2020 objectives, but also highlighted by numerous international organisations, has the human capital at its core, considered to be one of the strategic values of an organisation. In this context, the maximum-efficiency use of the human capital and its knowledge intensive development are envisaged. Since organisations are more and more interested in having people who are able, creative and highly motivated, this paperwork meets the current scientific needs and concerns. The purpose of this paper is to investigate whether there are differences between the work motivation of young people and adults. In the literature, there are two major extreme positions: there are theories that highlight the progress in the sphere of personality, during adulthood, on the one hand and, on the other hand, there are theories that focus on reducing the physical and psychological capacities, especially starting with the second sub-stage of adulthood, respectively 45-55 years old. As such, motivation is an important component of personality and thus we wish to examine whether motivation at work varies depending on the person’s bio-psycho-social development stage. For the processing of the data we used the computer software SPSS Statistics 23. For conducting the research we used the t test for two independent samples (Independent-Samples T Test). The dependent variable, motivation at work is, in our case, the numerical variable. For collecting the data for this variable on the interval - report Scale, we built a questionnaire regarding motivation at work. It had as basis the motivational theories based on the study of needs, respectively the ERG theory (Existence, Relatedness, Growth) proposed by Alfred (1972). Therefore, the three factors of the questionnaire were: motivation driven by the needs of existence, namely the physiological and safety needs, motivation driven by the needs of networking, affiliation and motivation driven by the needs of development, respectively needs of self-actualisation and esteem needs. The questionnaire contains 20 questions and it was applied on 60 subjects, employees of the same company, as follows: 30 subjects falling in the age group: 25-34 and 11 months years old, which means young people and 30 subjects with ages between 35 and 55 years old, which means adults. We chose to apply the questionnaire in the same company in order to eliminate the differences that might have arisen in the respondents’ answers due to the different management styles applied in several organisations. The volume of the sample allowed the use of the t test for two independent samples. The numerical variable was approximately normally distributed, within each group. The criteria of the statistical decision were established for α = 0.05 bilaterally. In order to be able to trust the test scores, we checked the test reliability, through the internal consistency analysis method. We calculated the inter-item consistency using the Cronbach Alpha coefficient. In the pre-test stage, we removed those items that had a negative correlation with the overall score and the items with an extremely low correlation with the global score. For each group we calculated the average (mean value) and the standard deviation. For higher reliance, we also calculated the reliance intervals for the difference between the mean values, as well as the effect-size indicator. Levene’s test for the equality of the variances allowed us to take the statistical decision of demonstrating the hypothesis of this research. The main results of the research consist of providing a scientific tool, based on which we can identify the degree of work motivation within the organization. Another important outcome of this research highlights the fact that there are major differences in terms of the employees’ motivation, depending on the age group they belong to, respectively youth or adulthood. In this paper we have also presented the possible scientific explanations for this phenomenon.